Problemer ved at oversætte Bibelen til dansk på ny - Jeppesen, Knud (HERMES - Journal of Language and Communication in Business, 1990)
In November 1989 the last issues of a trial translation to a forthcoming authorized Danish Bible version were released. The author, one of the editors of the translation, describes some of the problems connected to translating a text which already has a history in Danish language and literature and at the same time is dear to many people. A short introduction to the history of Bible translation in Denmark is given. The transmission of the text and the relation to the classic versions are touched upon, and finally some examples of changes from older translations to the new are discussed.